2013
DOI: 10.1039/c3ta12789c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of graphene hollow spheres for application in supercapacitors

Abstract: We have successfully assembled graphene nanosheets into spherical shells using polystyrene spheres as templates. Compared with stacked planar graphene, the as-prepared graphene spherical shells have more free space in between the spheres, which results in a larger accessible surface area for adsorption of electrolyte ions in supercapacitors. Electrochemical tests show that the graphene hollow spheres exhibit a high specific capacitance of 273 F g À1 and excellent electrochemical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Graphene, a single layer graphite with closely packed conjugated hexagonal lattices, has become a promising candidate for a broad range of applications due to its superior conductivity, large specific surface area, excellent mechanical flexibility, and high chemical stability [19][20][21][22][23]. Moreover, it not only presents high catalytic activity, longterm stability, and excellent physical and chemical properties but also contains the advantages of low cost and environment-friendliness [24].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a single layer graphite with closely packed conjugated hexagonal lattices, has become a promising candidate for a broad range of applications due to its superior conductivity, large specific surface area, excellent mechanical flexibility, and high chemical stability [19][20][21][22][23]. Moreover, it not only presents high catalytic activity, longterm stability, and excellent physical and chemical properties but also contains the advantages of low cost and environment-friendliness [24].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] For example, we have recently reported that graphene-based electrodes could exhibit high energy densities of 80-150 Wh kg -1 in IL electrolyte. [24][25][26][27][28] However, apart from the relatively high cost, there still exists another obstacle for the application of IL as the electrolyte for supercapacitors. Compared with aqueous electrolytes, ILs usually have larger molecules, lower conductivity, and higher viscosity, graphene supercapacitors often exhibit lower rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of graphene, it suffers from the serious agglomeration and restacking of neighboring graphene sheets due to van der Waals interactions [24]. Rational design of structure such as porous graphene [25], hierarchical sandwich-type graphene [26] and graphene hollow sphere [27,28] has been proven to be a good way to prevent the agglomeration of graphene and maintain its inherent properties.…”
Section: Introductionmentioning
confidence: 99%